2016
DOI: 10.3390/e18060226
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Crystallization of High-Entropy Amorphous NbTiAlSiWxNy Films Prepared by Magnetron Sputtering

Abstract: High-entropy amorphous NbTiAlSiW x N y films (x = 0 or 1, i.e., NbTiAlSiN y and NbTiAlSiWN y ) were prepared by magnetron sputtering method in the atmosphere of a mixture of N 2 + Ar (N 2 + Ar = 24 standard cubic centimeter per minute (sccm)), where N 2 = 0, 4, and 8 sccm). All the as-deposited films present amorphous structures, which remain stable at 700˝C for over 24 h. After heat treatment at 1000˝C the films began to crystalize, and while the NbTiAlSiN y films (N 2 = 4, 8 sccm) exhibit a face-centered cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 26 publications
3
30
0
1
Order By: Relevance
“…magnetron sputtering [34][35][36], laser cladding [37,38], spraying [39], electrodeposition [40], plasma-transferred arc cladding [41], and others. The present experimental results have proved that HEA films and coatings can show excellent mechanical and physical properties, such as the high hardness and elastic modulus [42,43], superior wear resistance [44], corrosion [45] and temperature resistance [46], as well as the appealing electrical [47] and magnetic properties [48].…”
Section: Introductionsupporting
confidence: 55%
“…magnetron sputtering [34][35][36], laser cladding [37,38], spraying [39], electrodeposition [40], plasma-transferred arc cladding [41], and others. The present experimental results have proved that HEA films and coatings can show excellent mechanical and physical properties, such as the high hardness and elastic modulus [42,43], superior wear resistance [44], corrosion [45] and temperature resistance [46], as well as the appealing electrical [47] and magnetic properties [48].…”
Section: Introductionsupporting
confidence: 55%
“…Another significant potential application of high-entropy films is as diffusion barriers [144]. Sheng et al [145] proposed huge application potentials of high entropy films in the fields of solar thermal conversion systems.…”
Section: Figure 19mentioning
confidence: 99%
“…Besides composition, fabrication methods can also affect the microstructure and mechanical properties of HEAs [20,21]. Magnetron sputtering and laser cladding are two of the most important methods for preparing HEA coatings [22][23][24][25][26][27][28]. Both N 2 flow rate and substrate bias affect hardness, the elastic modulus, and corrosive resistance of HEA coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al [32] used direct-current (DC) bias magnetron sputtering amorphous NbTiAlSiNx films with high hardness and modulus. The microstructures of the films are amorphous, and the microstructures are transformed into crystal structures at temperatures above 1000 • C. Sheng et al [23] reported that amorphous NbTiAlSiW x N y HEA films have high hardness and modulus, and are thermally stabile up to 700 • C, whereas the films transformed into crystal structures at temperatures greater than 1000 • C. Xing et al [33] reported that NbTiAlSiZrN x HEA films sputtered by direct current power had good thermal stability at 600 • C. The Cr 6 Fe 6 V 6 Ta 42 W 40 multicomponent alloy film exhibited great solar absorption at room temperature [34]. The (Al 0.5 CrFeNiTi 0.25 )N x HEA nitride films achieved higher hardness and Young's modulus than as-cast (Al 0.5 CrFeNiTi 0.25 )N x bulk alloys [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation